RecessionRisk+: A Novel Recession Risk Model with Applications to the Solvency II Framework and Recession Crises Forecasting - Jacopo Giacomelli; Luca Passalacqua (Mathematics)
The Solvency II regulatory framework requires European insurance companies to guarantee their solvability and stability by retaining enough Own Funds to cover future unexpected losses at a given confidence level. A Standard Formula approach is provided to estimate the capital requirement needed. Still, Solvency II allows internal methodologies to quantify the capital absorption arising from specific risk types or even to replace the Standard Formula with a full internal model. This work proposes a new internal model approach to measure the Catastrophe Recession Risk. The Recession Risk implies a mandatory capital absorption component for the insurance companies operating in the credit and suretyship business. The proposed model is based on the CreditRisk+ model and designed to behave countercyclically, aligning with the original intent of the European supervisory authority when first introducing this risk into the Solvency II risks’ taxonomy. Additionally, the model is applied to define an index for monitoring future recession crises based on the time series of past default rates.